An investigation into the factors affecting performance of fuzzy logic systems - Benatar, Naisan Ridvan (2015)
Fuzzy logic is a frequently used solution to control problems, especially when there are elements of human knowledge that may be incorporated into the system. Fuzzy logic comes in several varieties with the most common being based on either type-1 or type-2 fuzzy logic. Modifications to these standard varieties, termed Non-Stationary (NS) and Dual Surface (DS) are also investigated. Each variety allows a certain amount of flexibility in its expression. However, with this increased flexibility (and potentially performance) comes additional resource requirements: either during run time with higher processing and memory requirements; or at design time, with additional parameters requiring selection and optimisation.